Problematika Pengembangan Padi Organik di Sawangan Magelang serta Peluang Sertifikasi Internasional - Subejo PhD; Irham Irham; Pinjung Nawang Sari; Arif Wahyu Widada; Azizatun Nurhayati; Laksmi Yustika Devi; Esti Anatasari (Universitas Gadjah Mada, 2019)
Organic farming has been remarkably evolving in many areas of Indonesia for responding environmental issues and producing healthy foods. Organic rice is a type of organic farming product of a system which has been widely practiced including in Sawangan Village Magelang District as one of pioneering area on organic rice development in Central Java Province. This study is directed to analyze supporting factors, various problems faced on the development of organic rice and opportunity for getting international organic certification. A study has been done through household interview (30 farmers), indepth interview with key informants and Focus Group Discussion (FGD) at agricultural office of Magelang District. Data analysis used in this study are statistical descriptive and categorical qualitative. Results of the study show that: (1) performance of organic rice gradually getting better and productivity level has been getiing closer to conventional high external input rice farming, (2) supporting factorson improvement of organic rice include healthy rice production initiated through integrated pest management,transformative group leadership, supports from related stakeholders, high economic incentive, improvement of market networking, product certification, ICT application and favourable natural resource endowment, (3) Problems faced on the development of organic rice include variety of product quality among farmers, price variety and fluctuation, difficulty in organic seed access, mixing area of organic and anorganic rice farming, (4) Strategies for improving opportunity to get international organic sertification include innovation on product diversification, application of fresh product certification, modernization of machine for rice processing.